2016
DOI: 10.1371/journal.pntd.0004509
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Bartonella species Infection in Blood Donors from Southeast Brazil

Abstract: Bacteria from the genus Bartonella are emerging blood-borne bacteria, capable of causing long-lasting infection in marine and terrestrial mammals, including humans. Bartonella are generally well adapted to their main host, causing persistent infection without clinical manifestation. However, these organisms may cause severe disease in natural or accidental hosts. In humans, Bartonella species have been detected from sick patients presented with diverse disease manifestations, including cat scratch disease, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 30 publications
(38 reference statements)
2
26
0
3
Order By: Relevance
“…This genus has been increasingly associated with a wide spectrum of zoonotic emerging and reemerging infectious diseases. The number of validated species (more than 35), potential species (at least 17) and subspecies (at least three) continues to increase <http://www.bacterio.net/bartonella.html>. Some species, such as B. bacilliformis, cause potentially life threatening illness, but are limited geographically by the transmitting vector, whereas other species such as B. quintana are transmitted under poor hygienic conditions throughout the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This genus has been increasingly associated with a wide spectrum of zoonotic emerging and reemerging infectious diseases. The number of validated species (more than 35), potential species (at least 17) and subspecies (at least three) continues to increase <http://www.bacterio.net/bartonella.html>. Some species, such as B. bacilliformis, cause potentially life threatening illness, but are limited geographically by the transmitting vector, whereas other species such as B. quintana are transmitted under poor hygienic conditions throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Under a One Health prism, the collective understanding of Bartonella epidemiology and pathogenesis continues to change [13]. After recent studies in Brazil documented Bartonella infection (positive PCR/DNA sequencing results) in healthy blood donors [15][16][17], the authors initiated this study to assess the prevalence of Bartonella spp. infection in sanitary workers in a localized region of Spain.…”
Section: Introductionmentioning
confidence: 99%
“…are mostly limited to endemic regions, the data concerning the occurrence of anti-Bartonella spp. antibodies in healthy populations is scarce [25]. Seroprevalence may differ by region, e.g., 16.1% of blood donors in Sweden were found to be seropositive to all Bartonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…No medical organizations back any of these websites, nor do the websites cite any published medical literature supporting the accuracy of their information. Although scientific studies have found tick bites to be a risk factor for infection with Bartonella species, the capacity for ticks to transmit B. henselae is the subject of substantial debate . It is important for primary care providers to be aware of these online forums, because they often underlie parental concerns.…”
Section: Discussionmentioning
confidence: 99%